A morphological and phylogenetic characterisation of Inocybe similis (Agaricales, Inocybaceae), a rare species described by Bresadola in 1905 - Dovana, Francesco; Ferisin, Giuliano; Bizio, Enrico; Bandini, Ditte; Olariaga, Ibai; Esteve-Raventós, Fernando (Phytotaxa, 2020)
Inocybe similis, a very rare smooth-spored species originally described from Italy by Bresadola, is illustrated. Based on sequence generated from the type specimen, freshly collected specimens from five sites, Grado in north-east Italy, Tolmin in Slovenia, Forchach and Rieden in Austria and Füssen in Gemany could be asigned to I. similis and a more detailed description is provided here. The macro- and micromorphological features of I. similis suggest this species should be placed in Inocybe sect. Splendentes according to Singer´s classification. In contrast, our phylogenetic analyses support instead that I. similis belongs to Inocybe sect. Marginatae. From a morphological point of view, I. similis is close to I. vulpinella, but it is phylogenetically close to I. flavobrunnescens in sect. Marginatae.